Notice of Retraction: The Characteristic of toddler’s reproductive health in Posyandu Matahari, Blimbing, Malang - Kurnia Penta Seputra; Besut Daryanto; Zen Ary Prasetyo; Johannes Dwi Meiyanto (Brawijaya Journal of Urology, 2022)
This article has been retracted by the publisher. ----------------------------------------------------------------------- This article has been retracted at the request of the Authors. The editors and authors have jointly made the decision to retract the paper. Reasonable effort should be made to remove references to this paper. ----------------------------------------------------------------------- Objectives. The screening of reproductive health plays an essential role in early detection of reproductive health disorder. There was a study which suggested that there was at least one congenital disorder every 100 live births. Congenital reproductive disorders are mostly found in type of hypospadias, enlarged clitoris, micropenis, fusion of labia majora, and genital ambiguity. Data collected in Saiful Anwar General Hospital revealed that during the period of 2012-2017 there were 109 hypospadias cases, 64 undescended testicle cases, and 80 cases of testicular torsion. However, for the Disorders of Sex Development cases, there were 12 cases from the period of 2015-2017, with the mean age was school age (8-14 years old). Unfortunately, there was no data of congenital reproductive disorder in toddlers, thus we conducted screening of toddlers reproductive health in Posyandu Matahari which located in Gedung Serbaguna Rw. 14, Kelurahan Bunulrejo, Kelurahan Jodipan, Kecamatan Blimbing, Malang in order to find out the number of incidence of toddlers congenital reproductive disorder and held the early detection.Methods. This is observational descriptive study. Screening was held in Posyandu Matahari which is located in Gedung Serbaguna Rw. 14, Kelurahan Bunulrejo, Kelurahan Jodipan, Kecamatan Blimbing, Malang, on October 27, 2018. It used a method of physical examination (age, weight, height, external genital examination), and if it was found suspicious of disease or disorder of toddler congenital reproductive health, thus it would be given referral to appropriate health care.Results. This screening event involved 46 toddlers (1-5 years old). From 46 toddlers, there were 14 toddlers (30.43%), 10 toddlers suffered from Phimosis (21.74%), 1 toddler with Hydrocele (2.17%), dan 3 toddlers suffered from Undescended Testis (UDT) (6.52), who were referred to urology clinic in Saiful Anwar General Hospital to undergo further examination and treatment.Conclusions. The incidence of toddlers reproductive disorder of this event was 30,43%, showing that this age group (1-5 years old) had a significant amount of congenital reproductive disorder and screening played an important role for early detection and improving parental knowledge to prevent the delay of treatment for reproductive disorder.